Is a pleural on-call service beneficial? - Asciak, R; Hallifax, R; Mercer, R; Corcoran, J; Wrightson, J; Hassan, M; Bradley, C; Psallidas, I; Rahman, N (BMJ Publishing Group, 2017)
Aim: To audit the pleural on-call service referrals and outcome.